2022
DOI: 10.1111/rda.14142
|View full text |Cite
|
Sign up to set email alerts
|

Immunological uterine response to pig embryos before and during implantation

Abstract: From an immune point of view, the female reproductive tract is extremely dynamic. It is able, during the different stages of the estrous cycle, to adapt its immune response to hormonal changes and to the presence of semen and conceptus, preparing the uterine environment for pregnancy (Chase & Kaushik, 2019;Lin et al., 2015). The first preparatory events occur immediately post-mating in response to semen stimuli (seminal plasma and spermatozoa), being early and essential determinants of successful pregnancy pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The unique proteins involved in the immune system of PS are of particular interest, given that the modulation of the endometrial immune system is crucial for endometrial function and implantation [ 9 , 22 ]. Among the 53 PS-unique proteins annotated, 10 proteins were involved in cytokine signaling in immune system pathway in ClueGo analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique proteins involved in the immune system of PS are of particular interest, given that the modulation of the endometrial immune system is crucial for endometrial function and implantation [ 9 , 22 ]. Among the 53 PS-unique proteins annotated, 10 proteins were involved in cytokine signaling in immune system pathway in ClueGo analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the mid-implantation stage (d 18) is characterized by an increase in pro-inflammatory cytokine expression, which facilitates embryo implantation interactions between the placenta and uterus during porcine pregnancy [ 23 , 24 ]. Conversely, during the late implantation phase (d 20–28), anti-inflammatory expression is observed to support placental and conceptus development [ 22 ]. Practically all identified PS-unique proteins involved in immune system process were pro-inflammatory proteins, with the exception of HMOX1, which has anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…The H&E staining results showed dynamic changes in the placental structure across p21, p28, and p35. Embryo attachment is completed on day 18 in pigs, and then, the placenta begins to form [ 36 ]. Our study showed that trophoblast thickness constantly increased from p21 to p35.…”
Section: Discussionmentioning
confidence: 99%
“…The implantation of an embryo for pregnancy initiation represents the most important stage in the onset of pregnancy and involves a process of superimposition of a blastocystderived signature onto the receptive endometrium during the mid-secretory phase of the menstrual cycle, the so-called "window of receptivity". Both a receptive endometrium and timely signaling between the blastocyst and endometrium determine the success of implantation [17]. For instance, such endometrial factors as calcitonin [18], lysophosphatidic acid (LPA) [19], heparin-binding epidermal growth factor (HB-EGF) [20], leukemia-inhibiting factor (LIF) [21], and epidermal growth factor (EGF) [16] promote embryo implantation.…”
Section: Discussionmentioning
confidence: 99%